Emerging techniques and efficacy of endoscopic esophageal reconstruction and lumen restoration for complete esophageal obstruction - Perbtani, Yaseen; Suarez, Alejandro L.; Wagh, Mihir S. (Endoscopy International Open, 2016)
Background and study aims: Complete esophageal obstruction (CEO) is a rare occurrence characterized by progressive esophageal stricture, which eventually causes lumen obliteration. With recent advances in flexible endoscopy, various innovative techniques exist for restoring luminal continuity.The primary aim of this study was to assess the efficacy and safety of patients undergoing combined antegrade-retrograde endoscopic dilation for CEO at our institution. The secondary aim was to review and highlight emerging techniques, outcomes, and adverse events after endoscopic treatment of CEO. Patients and methods: Our electronic endoscopy database was retrospectively reviewed to identify patients who underwent combined antegrade and retrograde endoscopy for CEO. Patient and procedural data collected included gender, age, technical success, pre- and post-dysphagia scores, and adverse events. Results: Six patients (67 % male, mean age 71.6 years [range 63 – 80]) underwent technically successful esophageal reconstruction with combined antegrade-retrograde endoscopy. All patients noted improvement in dysphagia with mean pre-procedure dysphagia score of 4 reduced to 1.33 (range 0 – 3) post-procedure. There were no adverse events and mean follow-up time was 17.3 months (range 3 – 48). Conclusions: Combined antegrade and retrograde endoscopic therapy for CEO is feasible and safe. We present our experience with endoscopic management of complete esophageal obstruction, and highlight emerging techniques, outcomes and adverse events related to this minimally invasive modality.